Peningkatan Kapasitas Petani Melalui Penerapan Sistem Jajar Legowo pada Budidaya Jagung (Zea Mays) di Kecamatan Maja Kabupaten Majalengka - Chintiani Sukirman; Rudi Hartono; Nazaruddin (Jurnal Penyuluhan Pertanian, 2022)
Corn is a commodity located in Majalengka Regency is needed for many industries. According to data from the Central Statistics Agency, the Productivity of maize the average is in the District of Majalengka at 7,95 tons/ha, while the average productivity of maize in the District of Maja Majalengka range of 7.4 tons/ha. It can be argued that the productivity of corn in the District of Maja is still below the average of t h e Majalengka Regency. This study aims to describe the level of capacity of the farmers, knowing the influence of capacity building of farmers, to analyze the differences in growth between the use of the system jajar legowo the cultivation of corn and maize cultivation conventional and describe a strategy to increase the capacity of the farmers. The study involved 62 samples from 162 the population is scattered in Villages Anggrawati, Cipicung, and Wanahayu. The instrument in this research consists of the independent variable. As well as the dependent variable. Data analysis used is descriptive analysis, multiple linear regression, and one[1]way ANOVA. The level of farmer capacity in the implementation of the jajar legowo system in Maja District is in the medium category, namely 79%. The strategy for increasing the capacity of farmers is based on the results of descriptive analysis, namely counseling on corn cultivation using the jajar legowo system and bookkeeping in farming activities.